Emergency endovascular treatment of petrous carotid artery false aneurysm - Francesca Graziano, MD; Mario Ganau, MD, PhD; Vittorio M. Russo, MD; Domenico Gerardo Iacopino, MD, PhD; Arthur J. Ulm, MD, PhD (Interdisciplinary Neurosurgery, 2015)
Introduction: The management of ruptured intracranial false aneurysms (IFAs) might be tricky as any kind of treatment modality, surgical or endovascular, is burdened with significant challenges. A case report of the endovascular treatment of IFA in emergency setting is presented to provide more understanding of its pathophysiology as well as of the best operative work-up for petrous carotid artery reconstruction. Methods: Technical notes from a left sided skull base abscess, involving and eroding the carotid canal and petrous carotid artery (PCA) resulting in an IFA are shown and analyzed. Results: Balloon-assisted low viscosity Onyx embolization seems an effective method for the emergency treatment of IFA. Indications, technical nuances, and peri- and post-procedural complications are thoroughly discussed. A flow chart for the management of IFA is also proposed. Conclusions: The combination of parent artery balloon protection and low viscosity Onyx embolization can provide an effective occlusion of the IFA while maintaining parent artery patency. Normal distal filling of the parent artery, and optimal obliteration of the IFA are easily achievable.